Personal Branding Syifa Adinda Negara melalui Instagram - Ramadhani, Nabilah; Anugrah, Dadan; Wibawa, Darajat (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This Study aims to find out Syifa Adinda Negara’s personal branding throuh her instagram social media acount is related to the character, visibility and quality of Syifa Adinda Negara’s personal branding on instagram. The Research method used is a descriptive study with in-depth interview data collection techniques, non-participant observation and documentation. The resluts of the study show that Syifa Adinda Negara’s personal branding on instagram is: 1) Character there are four laws of personal branding, namely specialization, leadership, personality and distinctiveness. 2) Visibility there are two laws of personal branding, namely visibility and unity. 3) Quality there are two laws of personal branding, namely persistance and good will.